2010
DOI: 10.1002/jctb.2332
|View full text |Cite
|
Sign up to set email alerts
|

A hollow fiber membrane photo‐bioreactor for CO2 sequestration from combustion gas coupled with wastewater treatment: a process engineering approach

Abstract: BACKGROUND: In the presence of light, micro-algae convert CO 2 and nutrients to biomass that can be used as a biofuel. In closed photo-bioreactors, however, light and CO 2 availability often limit algae production and can be difficult to control using traditional diffuser systems. In this research, a hollow fiber membrane photo-bioreactor (HFMPB) was investigated to: (1) increase the interfacial contact area available for gas transfer, (2) treat high nutrient strength (412 mg NO 3 − -N L −1 ) wastewater, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 56 publications
(53 reference statements)
3
40
0
1
Order By: Relevance
“…Kumar et al (2010) used algae, Spirulina platensis, to fix carbon dioxide from gas mixtures with carbon dioxide contents of 15%, 30%, and 100% (v/v), respectively, and observed that algae productivity was reduced, and even the death of algae occurred during the long term cultivation with these high carbon dioxide concentrations. On the contrary, some studies reported that some algae such as Chlorella vulgaris, Chlorococcum littorale, and Scenedesmus sp., could tolerance to high carbon dioxide concentration (13%, 60%, and 80% (v/v)) (Hanagata et al 1992;Kodama et al 1993;Douskova et al 2009).…”
Section: Carbon Dioxide Concentration and Transportation Effectmentioning
confidence: 99%
“…Kumar et al (2010) used algae, Spirulina platensis, to fix carbon dioxide from gas mixtures with carbon dioxide contents of 15%, 30%, and 100% (v/v), respectively, and observed that algae productivity was reduced, and even the death of algae occurred during the long term cultivation with these high carbon dioxide concentrations. On the contrary, some studies reported that some algae such as Chlorella vulgaris, Chlorococcum littorale, and Scenedesmus sp., could tolerance to high carbon dioxide concentration (13%, 60%, and 80% (v/v)) (Hanagata et al 1992;Kodama et al 1993;Douskova et al 2009).…”
Section: Carbon Dioxide Concentration and Transportation Effectmentioning
confidence: 99%
“…5 The production of photosynthetic microorganisms has been carried out both in open ponds and engineered photobioreactor systems, such as vertical, horizontal or helicoidal tubular reactors, 6,7 flat-plate reactors 8 or membrane photobioreactors. 9 Tubular reactors provided with the airlift system 10 are among the most popular types because of the satisfactory gas transfer and light utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Algae production has been carried out in both open ponds and engineered photobioreactor systems, such as vertical or horizontal tubular reactors (Sánchez Mirón et al, 2000;Barbosa et al, 2004), flat-plate reactors (Morita et al, 2000) or membrane photobioreactors (Kumar et al, 2010b). Vertical tubular reactors, such as airlift bioreactors, are among the most popular types of photobioreactors because they provide good gas transfer and light utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…An air or CO 2 /air mixture is bubbled into the reactor at the base of the riser to separate the reactor volume into gassed and ungassed regions. Flue gases from power plants have also been proposed to provide a more sustainable supply of CO 2 to the algae and reduce greenhouse gas emissions (Kumar et al, 2010b). Liquid circulation is induced by the hydrostatic disequilibrium caused by the density difference between the riser and the downcomer.…”
Section: Introductionmentioning
confidence: 99%